Continuously Varying Thickness Interference Bandpass Filter for the Visible Spectral Range: Using Ion Beam Sputter Deposition - Anayat Ullah; Muhammad Rizwan Amirzada; M. D. Rifat Jahan; Yousuf Khan (Advances in Materials Science and Engineering)
Optical bandpass filters, used to restrict certain wavelengths while allowing other wavelengths to pass, are a common element in many optical devices, such as spectroscopic sensors and hyperspectral imagers. Such filters can be implemented using interference filters, which operate on the principle of constructive and destructive interference. In this work, an interference bandpass filter with continuously varying thicknesses of the constituent films is designed and fabricated for the visible spectral range. Niobium pentoxide and silicon dioxide are used as the filter materials due to the high refractive index contrast between them, resulting in a smaller number of required material films. Ion beam sputter deposition is used as the deposition method due to its ability to produce accurate thickness high optical quality films. The fabricated filter has a transmission band of 130 nm, i.e., 470–600 nm, and can block wavelengths as low as 300 nm and as high as 1080 nm, which is sufficient for use with silicon-based detectors in the visible spectral range. The maximum and minimum transmission inside the transmission band is 96% and 71%, respectively, with an average transmission of 88%. The transmission outside the transmission band is less than 1.6%.